2022
DOI: 10.1002/cplu.202200212
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy‐Functionalized Hypercrosslinked Polymers (HCPs) as Dual Phase Radioactive Iodine Scavengers: Synergy of Porosity and Functionality

Abstract: Large-scale nuclear power plant production of iodine radionuclides ( 129 I, 131 I) pose huge threat in the events of nuclear disaster. Effective removal of radioiodine from nuclear waste is one of the most critical challenge because of the drawbacks of state-of-the-art adsorbents such as high cost, low uptake capacity and non-recyclability. Herein, two hydroxy-functionalized (-OH) hypercrosslinked polymers (HCPs), namely HCP-91 and HCP-92, have been synthesized and employed towards capture of iodine. High chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…In another report from our group, demonstration of the role of the -OH group in synergy with porosity in the effective capture of iodine from both vapour phase and water medium has been explored by synthesizing three HCPs (HCP-91, HCP-92 and non-functionalized biphenyl HCP). 300 ), etc. as potential hazardous inorganic pollutants in wastewater on the priority list.…”
Section: Pollutant Sequestration From Watermentioning
confidence: 99%
“…In another report from our group, demonstration of the role of the -OH group in synergy with porosity in the effective capture of iodine from both vapour phase and water medium has been explored by synthesizing three HCPs (HCP-91, HCP-92 and non-functionalized biphenyl HCP). 300 ), etc. as potential hazardous inorganic pollutants in wastewater on the priority list.…”
Section: Pollutant Sequestration From Watermentioning
confidence: 99%
“…synthesized two hydroxy-functionalized (-OH) hypercrosslinked polymers (HCPs) and demonstrated that the hydroxyl groups in the polymers can form H-bonding with iodine and triiodide ions which further enhanced the iodine removal efficiency from water. 36 Neeladri Das et al. reported a facile triptycene based hydroxyl Azo-nanoporous polymer and the presence of phenolic-OH in the polymer enable it effective for iodine capture (1.88 g g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…By far, adsorption is regarded as an effective strategy for radioiodine removal due to advantages such as easy operation, high efficiency, low cost, and so on. In recent years, various adsorbent materials have been developed for iodine capture, including inorganic zeolites [7,8], activated carbon [9,10], and silver-doped mordenite [11], as well as organic-inorganic hybrid materials (mainly referring to metal-organic frameworks, MOFs [12][13][14][15]), and organic porous framework materials such as covalent organic frameworks (COFs) [16][17][18][19][20], conjugated microporous polymers (CMPs) [21][22][23][24], porous aromatic frameworks (PAFs) [25][26][27], porous organic frameworks (POFs) [28], hyper crosslinked polymers (HCPs) [29,30], etc. Among them, organic porous framework materials appear to be one of the most effective adsorbents for iodine capture [5].…”
Section: Introductionmentioning
confidence: 99%